PUNCAK KLIMAKS CAPAIAN SUFISTIK DALAM PERSPEKTIF TASAWUF - Ilham, Muh. (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
A Sufi has his own way (tariqah) in his spiritual journey. The difference of tariqah pursued by the Sufis creates schools of Sufism. However, one thing is mutually agreed that all the Sufi with various tariqah towards one goal, namely ma’rifatullah. This article will examine the process of achieving the Sufis in makrifatullah by passing comparative studies between one school with another. Through the analysis of some literature tasawuf researchers conclude that each Sufi has a distinctive tariqah in reaching the peak makrifatullah. In addition, all schools also have a tendency that the common tariqah that must be passed is the takhalli, tahalli and tajalli stages.